Figure 160. Telegraph Instruments - Croft, Terrell (Practical Electricity, 1917)
Diagram depicting the different components of a telegraph, including the key, sounder, and relay.
Keywords: Communication; Communication and technology; Electrical engineering; Electricity; Telecommunication; Telegraph; Telegraph lines